e-CRM and e-Loyalty: A Case Study in Kuala Lumpur Metropolitan University College (KLMUC) - Abdullah, Siti Salmiah; Abdul Wahid, Nur Kamariah (IIUM Journal of Case Studies in Management, 2025)
The emergence of technology in the modern world has profoundly transformed various aspects of life, industries, and society. It has led to substantial advancements and changes across various domains, enhancing efficiency, accessibility, and connectivity including in educational institutions. However, it also presents challenges that society must navigate, such as ethical concerns, potential job displacement, and the digital divide. e-CRM goes beyond traditional CRM by leveraging the internet, social media, mobile applications, and other online platforms to enhance customer engagement and experience. e-CRM in educational institutions plays a critical role in building strong students' relationships in the digital age, allowing students to enhance their loyalty, improve service delivery, and increase sales through better targeting and engagement strategies. This paper delves into the realm of electronic customer relationship management (e-CRM) in KLMUC that focusing on the impact of digital transformation on e-loyalty. With the advent of current situations, evolving expectations of tech-savvy students, establishing and maintaining e-loyalty has become crucial for private IHLs. This article explores the pivotal role of e-CRM in enhancing e-loyalty and presents it as a strategic imperative for businesses. Drawing on theoretical frameworks and empirical evidence, this research article provides insights into how businesses can leverage e-CRM to elevate their brand image, build customer trust, and foster long-term relationships. By understanding the significance of e-CRM as a catalyst for e-loyalty enhancement, KLMUC can develop effective strategies to thrive in today's dynamic marketplace. Key words: e-Loyalty, e-Customer Relationship Management, Institutes of Higher Learning